Maternal height, childhood growth and risk of hip fracture in later life: a longitudinal study. - Cooper, C; Eriksson, J; Forsén, T; Osmond, C; Tuomilehto, J; Barker, D (2001)
Although measures to enhance bone mineralization during childhood and adolescence are widely incorporated into preventive programmes against osteoporotic fracture, there are no published data directly linking growth rates in childhood with the risk of later hip fracture. We addressed this issue in a unique Finnish cohort in whom birth and childhood growth data were linked to later hospital discharge records. This permitted follow-up of 3639 men and 3447 women who were born in Helsinki University Central Hospital between 1924 and 1933, who went to school in Helsinki and still lived in Finland in 1971. Body size at birth was recorded and an average of 10 measurements were obtained of height and weight throughout childhood. We identified 112 subjects (55 men and 57 women) who sustained a hip fracture during 165 404 person-years of follow-up. After adjustment for age and sex in a proportional hazards model, we identified two major determinants of hip fracture risk: tall maternal height (p < 0.001) and a low rate of childhood growth (height, p = 0.006; weight, p = 0.01). The hazard ratio for hip fracture was 2.1 (95% CI 1.2-3.5) among men and women born to mothers taller than 1.61 m, when compared with those whose mothers were shorter than 1.54 m. The ratio was 1.9 (95% CI 1.1-3.2) among those whose rate of childhood height gain was below the lowest quartile for the cohort, compared with those whose growth rate was above the highest quartile. The effects of maternal height and childhood growth rate were statistically independent of each other, and remained after adjusting for socioeconomic status. The patterns of childhood growth that predicted future hip fracture differed between boys and girls. In boys, there was a constant deficit in height and weight between ages 7 and 15 years among those later sustaining fractures; in girls, there was a progressively increasing deficit in weight but a delayed height gain among those later sustaining fractures. This epidemiologic study provides the first direct evidence that a low rate of childhood growth is a risk factor for later hip fracture. Whether reduced growth rate is a consequence of childhood lifestyle, genetic background or intrauterine hormonal programming, the data support measures to optimize childhood growth as part of preventive strategies against osteoporotic fracture in future generations.